Hydrogels in Veterinary Vaccine Development: Types, Mechanisms, and Applications - Peisen Zhao; Yuwei Yang; Lingxue Yu; Guoxin Li; Dandan Zhu (Gels)
This review examines the potential and challenges of using hydrogel vaccine delivery systems in animal immunization. Traditional methods face issues like low immunogenicity, reliance on cold chains, and inefficient delivery, limiting their use in modern animal husbandry. Hydrogels offer a promising solution due to their biocompatibility, controlled drug release, and immune regulation. This paper highlights hydrogels’ benefits, such as mimicking natural infection through sustained antigen release, boosting antigen-presenting cell activity, activating immune responses, and forming barriers at mucosal sites to prevent pathogen invasion. Additionally, innovative delivery methods like microneedle patches and nasal sprays show promise in enhancing convenience and compliance in animal vaccination. By combining interdisciplinary efforts and technological advancements, the hydrogel vaccine delivery system is anticipated to be crucial in preventing animal diseases, supporting sustainable animal husbandry, and ensuring global animal health and food safety.